Corpo de conhecimento demandado ao bibliotecário pelo mercado de trabalho - Tinelli, Marcele Aparecida (Universidade Federal de São Carlos, 2010)
The labor market demands of the information professional librarian expertise in their area of expertise as well as related areas. In order to contribute to their training, the object of this study was to identify the body of knowledge required from the information professional librarian by the labor market through bibliometric analysis of a set of evidence procurement of São Paulo, period 2005 to 2009. The results were elaborated indicators on the intensity and distribution of knowledge required by the job market in relation to specialized topics of Information Science, organized into working groups according to the National Association for Research and Graduate Studies in Information Science (ANCIB) and still was able to see the similarities between the contracting organizations regarding the requisite expertise. The body of knowledge about the required knowledge can contribute to the training of professionals more closely aligned with the needs of the labor market and therefore of society.
Body of knowledge demanded of the librarian by the labor market
Keywords: Profissional da informação; Bibliotecário; Mercado de trabalho; Biblioteconomia e Ciência da Informação; Corpo de conhecimento; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO